A system-based approach for the design of laterally unbraced multi-span steel columns and beams. (15th March 2017) - Gonçalves, Rodrigo; Camotim, Dinar
Highlights: A rational and efficient system-based design approach is proposed. The slenderness of the system can be employed to characterise its buckling behaviour. Structural optimisation procedures are outlined. Abstract: This paper discusses aspects related to the determination of the buckling resistance of multi-span steel columns and beams in accordance with Eurocode 3 (EN 1993-1-1:2005, 2005). In particular, the paper reviews and extends the method previously proposed by the authors (Gonçalves and Camotim, 2005) for uniformly compressed members (columns) integrated in structural systems, which means that it is (i) system-based, i.e. relies on system parameters, and (ii) consistent with the Eurocode 3 buckling curves. It is shown that, besides making it possible to avoid individual member checks, the proposed approach provides relevant insight into the structural efficiency of the complete system. In order to illustrate the application of the proposed approach, several examples are presented and discussed throughout the paper. For comparison purposes, "exact" buckling (collapse) loads are provided, which are obtained from non-linear elastoplastic finite element analyses including member imperfections.